Discovery of a Role for Rab3b in Habituation and Cocaine Induced Locomotor Activation in Mice Using Heterogeneous Functional Genomic Analysis - Bubier, Jason A.; Philip, Vivek M.; Dickson, Price E.; Mittleman, Guy; Chesler, Elissa J. (Frontiers in Neuroscience, 2020)
Substance use disorders are prevalent and present a tremendous societal cost but the mechanisms underlying addiction behavior are poorly understood and few biological treatments exist. One strategy to identify novel molecular mechanisms of addiction is through functional genomic experimentation. However, results from individual experiments are often noisy. To address this problem, the convergent analysis of multiple genomic experiments can prioritize signal from these studies. In the present study, we examine genetic loci identified in the recombinant inbred (BXD RI) genetic reference population that modulate the locomotor response to cocaine. We then applied the GeneWeaver software system for heterogeneous functional genomic analysis to integrate and aggregate multiple studies of addiction genomics, resulting in the identification of Rab3b, as a functional correlate of the locomotor response to cocaine in rodents. This gene encodes a member of the RAB family of Ras-like GTPases known to be involved in trafficking of secretory and endocytic vesicles in eukaryotic cells. The convergent evidence for a role of Rab3b was included co-occurrence in previously published genetic mapping studies of cocaine related behaviors; methamphetamine response and Cartpt (Cocaine- and amphetamine-regulated transcript prepropeptide) abundance; evidence related to other addictive substances; density of polymorphisms; and its expression pattern in reward pathways. To evaluate this finding, we examined the effect of RAB3 complex perturbation in cocaine response. B6;129-Rab3btm1Sud Rab3ctm1sud Rab3dtm1sud triple null mice (Rab3bcd-/-) exhibited significant deficits in habituation, and increased acute and repeated cocaine responses. This previously unidentified mechanism of the behavioral predisposition and response to cocaine is an example of many that can be identified and validated using aggregate genomic studies.